2014
DOI: 10.4236/health.2014.612185
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Short Term Vitamin D Supplementation on the Inflammatory and Oxidative Mediators of Arterial Stiffness

Abstract: Background Vitamin D deficiency has been implicated as a potential risk factor for cardiovascular disease. The high rate of vitamin D deficiency (<30 ng/ml) exhibited by African Americans may account for some of the excess prevalence of cardiovascular morbidity and mortality in this vulnerable US population. Vitamin D supplementation may reduce the risk of cardiovascular disease by ameliorating the onset and progression of arterial stiffness, a strong predictor of cardiovascular mortality, usually assessed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 26 publications
0
41
0
Order By: Relevance
“…The results from RCTs on AIx are more contradicting; no improvement was reported in the majority of studies [61,62,64,71,72,77,83]. Alternatively, decreases in AIx were observed among patients with T2DM [66], overweight people with elevated BP [75], people with VitD deficiency [84] and those with pre-hypertension and VitD deficiency [85]. Conversely, 1 study reported significant increases in AIx in patients with T2DM and hypovitaminosis [63].…”
Section: Summary Of Rct Data On the Effect Of Vitd Supplementation Onmentioning
confidence: 98%
See 1 more Smart Citation
“…The results from RCTs on AIx are more contradicting; no improvement was reported in the majority of studies [61,62,64,71,72,77,83]. Alternatively, decreases in AIx were observed among patients with T2DM [66], overweight people with elevated BP [75], people with VitD deficiency [84] and those with pre-hypertension and VitD deficiency [85]. Conversely, 1 study reported significant increases in AIx in patients with T2DM and hypovitaminosis [63].…”
Section: Summary Of Rct Data On the Effect Of Vitd Supplementation Onmentioning
confidence: 98%
“…In terms of effects on BP, some RCTs have reported significant improvements in brachial BP after short-term supplementation of VitD among participants encompassing a variety of clinical characteristics, including patients with hypercalcaemia [53] or impaired glucose tolerance [54], patients with primary hyperparathyroidism [55], patients with T2DM [56,57,58], patients with elevated BP and VitD deficiency [59] and women with VitD deficiency [60]. However, the majority of RCTs have been ineffective in improving brachial BP in a range of populations as shown in Table 1[61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79]. Indeed, a recent individual-level meta-analysis of RCTs concluded that VitD was ineffective in lowering BP [80].…”
Section: Summary Of Rct Data On the Effect Of Vitd Supplementation Onmentioning
confidence: 99%
“…Moreover, our group shown previously that 1,25-D 3 is a potent anti-fibrotic factor promoting the decrease expression of TGF-β, PAI-1 and several collagen isoforms in mesenchymal multipotent cells There is an in vivo study showing that vitamin D deficiency results in maladaptive cardiac remodeling attributable to progressive myocyte hypertrophy and interstitial fibrosis (Meems et al, 2012). A recent study by our group did show repletion of hypovitaminosis D in humans led to down-regulation of protein expression in abdomen fat biopsies for tumor necrosis factor alpha, IFN gamma, interleukin 6 and soluble intercellular adhesion molecule-1 (sICAM-1), a biomarker of inflammatory process associated with endothelial damage and platelet activation, supporting an in vivo role for vitamin D in related signaling pathways (Martins et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a recent study performed on Framingham Offspring Heart Study participants [57], vitamin D 3 deficiency was associated with increased cardiovascular risk, above and beyond established cardiovascular risk factors. In another study, performed on elderly subjects, an association between low serum vitamin D 3 levels and high arterial blood pressure was found [58]. In addition, vitamin D 3 insufficiency/deficiency is associated with myocardial infarction, congestive heart failure, and calcific aortic stenosis, which can lead to the massive vascular calcification seen in chronic kidney disease.…”
Section: Cardiovascular and Cerebral Riskmentioning
confidence: 95%